PHYSICAL AND SPORTS EDUCATION BETWEEN 1965 AND 1975 IN FRANCE (Fiep Bulletin - online, 2014)
Physical and Sports Education in France between 1965 and 1975 went through a transformation that allows us to distinguish three currents: the psycho-kinetic, by Jean Le Boulsh; the one developed by FSGT (Federation Sportive et Gyminique du Travail) by authors such as Merànd, Deleplace, Mostard, Goirand; and the action of motor skills science, by Pierre Parlebas. The purposes of each of those currents, their scientific references and didactical procedures were presented. For the author, the duration between 1964 and 1975 is characterized in France as a central moment for the change of paradigms in Physical and Sports Education. That was the occasion that offered the new following periods the availability of the postulates from those three currents.